Analisis Search Engine Optimization (SEO) pada Layanan Sistem Informasi Ketenagakerjaan - Paulus Insap Santosa; Arif Budi Setiawan (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2021)
Sistem Informasi Ketenagakerjaan (Sisnaker) is the implementation of e-government at the Ministry of Manpower which is intended so that the public can easily access employment information and services. To find information, people usually use search engines. Sisnaker must be on the front page of the search engine page so that it is easily found by the public. This study analyzes the application of search engine optimization (SEO) on sisnaker with automated tools such as Google Analytics, Moz Pro and Ubersuggest. The method used is a descriptive method by describing the results obtained from the SEO automatic analysis tool. The result is that the implementation of SEO sisnaker is good, but some things need to be improved.